Solub + transp - LOAM.xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
The dissolution and transport of IHE particles with rainwater in a sandy loam soil in triplicates.
Keywords: 'dissolution and transport'; 'environmental science'; 'sandy loam soil'